2019
DOI: 10.14715/cmb/2019.65.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Allium sativum oil to alleviate tebuconazol-induced oxidative stress in the liver of adult rats

Abstract: The present study focused on the protective efficacy of Allium sativum oil (ASO) against tebuconazol (TEB)-induced oxidative stress in the liver of adult rats. Thirty-two rats were randomly divided into four groups of eight each: group I served as control rats, group II was treated with TEB (100 mg/kg bw), group III received ASO (5ml/kg bw). The animals of group IV were treated with TEB and ASO, during 4 weeks. The obtained results showed that TEB induced a significant change of some hematological parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Finally, to evaluate ASO-induced hepatotoxicity, serum levels of biomarkers alanine transaminase (ALT), aspartate transaminase (AST), albumin, and total bilirubin were measured. 56 As shown in Figure 5 D, no significant increases were observed in 993562- and 993563-treated groups for all four biomarkers, and only a moderate but not clinically precluding increase in serum ALT and AST levels (∼3- to 4-fold compared with PBS control) was observed in the 993523-treated group. Taken together, these results indicated that the selected SFT-ASOs 993523, 993562, and 993563 displayed acceptable in vivo tolerability profiles.…”
Section: Resultsmentioning
confidence: 74%
“…Finally, to evaluate ASO-induced hepatotoxicity, serum levels of biomarkers alanine transaminase (ALT), aspartate transaminase (AST), albumin, and total bilirubin were measured. 56 As shown in Figure 5 D, no significant increases were observed in 993562- and 993563-treated groups for all four biomarkers, and only a moderate but not clinically precluding increase in serum ALT and AST levels (∼3- to 4-fold compared with PBS control) was observed in the 993523-treated group. Taken together, these results indicated that the selected SFT-ASOs 993523, 993562, and 993563 displayed acceptable in vivo tolerability profiles.…”
Section: Resultsmentioning
confidence: 74%
“…The formation of the histological sections was carried out according to the method described by Berrouague et al (27). The lung was dissected and immediately fixed in a 10% formalin solution, treated with a series of graded ethanol, and then embedded in paraffin (increased at 56/58°C).…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…The province (department) of El-Tarf (North East of Algeria) runs along the Mediterranean over 90km. This coastline teems with wild medicinal and aromatic plants (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This harmonious greenery contains ecosystem variables and maintains the ecological stability of the region, which led to several inventories and researches on the vegetation of this region like the works of (16) as well as (17).…”
Section: Introductionmentioning
confidence: 99%